At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Hey Justinjames23m,
This is how you do it, step by step:
2(d - 6) = 3d + 5
2d - 12 = 3d + 5
2d = 3d + 17
d = -17
Hope this helps!
Chen :D
This is how you do it, step by step:
2(d - 6) = 3d + 5
2d - 12 = 3d + 5
2d = 3d + 17
d = -17
Hope this helps!
Chen :D
[tex]2(d-6)=3d+5\\\\2d-12=3d+5\\\\2d-3d=5+12\\\\-d=17\ /\cdot(-1)\\\\d=-17[/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.